2016
DOI: 10.5114/jcb.2016.63192
|View full text |Cite
|
Sign up to set email alerts
|

Salvage interstitial brachytherapy based on computed tomography for recurrent cervical cancer after radical hysterectomy and adjuvant radiation therapy: case presentations and introduction of the technique

Abstract: PurposeLocally recurring cervical cancer after surgery and adjuvant radiotherapy remains a major therapeutic challenge. This paper presents a new therapeutic technique for such patients: interstitial brachytherapy (BT) guided by real-time three-dimensional (3D) computed tomography (CT).Material and methodsSixteen patients with recurrent cervical cancer after radical surgery and adjuvant external-beam radiotherapy (EBRT) were included in this study. These patients underwent high-dose-rate (HDR) interstitial BT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 24 publications
(25 reference statements)
0
19
0
Order By: Relevance
“…Over the past 20 years, 14 retrospectives series, and one phase II prospective study with only few patients [ 31 ], reported clinical experiences of high dose rate (HDR) or low dose rate (LDR) 3D-IGBT in previously irradiated pelvic recurrences of gynecologic malignancies ( Table 1 ) [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. In nine of those, 100% of the population received prior BT, prior EBRT, or a combination of EBRT followed with BT [ 31 , 32 , 33 , 36 , 40 , 41 , 43 , 44 , 45 ]. In the six remaining articles, only a variable subset of patients (from 10% to 85.7% of the studied population) received IGBT in a re-irradiation setting [ 34 , 35 , 37 , 38 , 39 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Over the past 20 years, 14 retrospectives series, and one phase II prospective study with only few patients [ 31 ], reported clinical experiences of high dose rate (HDR) or low dose rate (LDR) 3D-IGBT in previously irradiated pelvic recurrences of gynecologic malignancies ( Table 1 ) [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. In nine of those, 100% of the population received prior BT, prior EBRT, or a combination of EBRT followed with BT [ 31 , 32 , 33 , 36 , 40 , 41 , 43 , 44 , 45 ]. In the six remaining articles, only a variable subset of patients (from 10% to 85.7% of the studied population) received IGBT in a re-irradiation setting [ 34 , 35 , 37 , 38 , 39 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The median follow-up was available in 12/14 studies (not reported in two [ 36 , 37 ]) and ranged from 16.3 to 55.6 months (median, 27.6 months).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations